Energy transfer in aggregates of bacteriochlorophyll c self-assembled with azulene derivatives - Matěnová, Martina; Lorelei Horhoiu, Viviana; Dang, Florian-Xuan; Pospíšil, Petr; Alster, Jan; Burda, Jaroslav V; Balaban, Teodor Silviu; Pšenčík, Jakub (Physical chemistry chemical physics, 2014)
Bacteriochlorophyll (BChl) c is the main light-harvesting pigment of certain photosynthetic bacteria. It is found in the form of self-assembled aggregates in the so-called chlorosomes. Here we report the results of co-aggregation experiments of BChl c with azulene and its tailored derivatives. We have performed spectroscopic and quantum chemical characterization of the azulenes, followed by self-assembly experiments. The results show that only azulenes with sufficient hydrophobicity are able to induce aggregation of BChl c. Interestingly, only azulene derivatives possessing a conjugated phenyl ring were capable of efficient (∼50%) excitation energy transfer to BChl molecules. These aggregates represent an artificial light-harvesting complex with enhanced absorption between 220 and 350 nm compared to aggregates of pure BChl c. The results provide insight into the principles of self-assembly of BChl aggregates and suggest an important role of the π-π interactions in efficient energy transfer.
Keywords: bakteriální proteiny; Energy Transfer; bakteriochlorofyly; azuleny; Bacterial Proteins; Azulenes; přenos energie; Bacteriochlorophylls